MEASUREMENT OF RNFL THICKNESS USING OCT IMAGES FOR GLAUCOMA DETECTION - Dhivyabharathi; Ganeshbabu; Venkatesh Rengaraj (ICTACT Journal on Image and Video Processing, 2013)
The thickness of retinal nerve fiber layer (RNFL) is one of the pompous parameters for assessing the disease, Glaucoma. A substantial amount of vision can be lost before the patient becomes aware of any defect. Optical Coherence Tomography (OCT) provides enhanced depth and clarity of viewing tissues with high resolution compared with other medical imaging devices. It examines the living tissue non-invasively. This paper presents an automatic method to find the thickness of RNFL using OCT images. The proposed algorithm first extracts all the layers present in the OCT image by texture segmentation using Gabor filter method and an algorithm is then developed to segment the RNFL. The thickness measurement of RNFL is automatically displayed based on pixel calculation. The calculated thickness values are compared with the original values obtained from hospital. The result shows that the proposed algorithm is efficient in segmenting the region of interest without manual intervention. The effectiveness of the proposed method is proved statistically by the performance analysis.